The Use of Choice Modelling in Assessing Tourists Destinations: A Case Study of Redang Marine Park (RMP) Malaysia - Shamsul Bahrain, Rawi (2012)
This study employs the Choice Modelling (CM) Technique, in particular the Contingent Ranking (CR) method, to measure the economic value of the Redang Marine Park (RMP) system in Malaysia. The reason for using CR is to understand which islands in the RMP system the tourists prefer. Knowing the islands’ ranking is crucial for the planning and development of this particular island as a tourism product and destination, and at the same time, for maintaining the islands’ ecosystem as a protected area. The study is divided into three major components. The first investigates destination choices amongst tourists. In this component, the attributes of interest include choices of island, types of accommodation available at the destination, facilities provided at the place of accommodation, distance of accommodation sites to the beach, and types of transportation used to reach the destination. These attributes are measured using the 3-day/2-night (3D2N) package prices offered as holiday packages to tourists. The second component measures the importance of environmental attributes, namely the status of available fish and coral species, the numbers of nesting turtles and the degree of congestion that the tourists experience while participating in water activities such as snorkelling and diving. These attributes are measured through the conservation fees collected by the park authority from tourists visiting RMP. The final part of this study is concerned with the members of local community on the island. Their perceptions towards tourism, their readiness to participate in tourism activities and their attitudes towards MP development are issues explored in this study. A total of 189 local tourists and 94 foreign tourists were interviewed in this CR study, while 200 local residents were interviewed in the community study. This study finds that, in terms of the choice of destination, different islands do matter and are statistically significant for both local and foreign tourists. In terms of overall ranking, both local and foreign tourists rank Kapas as their first choice, while Tenggol ranks last. The main attributes in the destination choice are statistically significant for local and foreign tourists, except for facilities provided at the sites of accommodation. WTP for almost all attributes concerned are higher for local tourists than for foreign ones, except for the reduction in distance between the accommodation sites and the beach. Specifically, the improvement in terms of types of accommodation ranges from RM113.33 to RM205.50 for local tourists and RM136.50 to RM169.71 for foreign tourists. WTP for improved travel time from the mainland to the island ranges from RM0.43 to RM1.75 for the domestic tourists, as opposed to the values given by foreign tourists, ranging from RM0.29 to RM1.50. WTP for the option of accommodation situated closer to beach areas ranges from RM3.14 to RM11.25 for local tourists. These values are lower than WTP given by foreign tourists, which range from RM10.55 to RM15.57. Further analyses on marginal WTP are also discussed. Regarding environmental issues, this study finds that all attributes are statistically significant for both local and foreign tourists. The local tourists’ WTP for changes in the number of fish and coral species ranges between RM4.31 to RM6.70, while foreign tourists’ WTP ranges between RM3.50 to RM6.73. As for the number of nesting turtles, locals are willing to pay between RM3.78 and RM4.76 while foreign tourists are willing to pay between RM2.28 and RM4.14 for different attribute levels. Finally to avoid congestion while participating in the water activities, WTP by locals ranges between RM2.80 to RM13.37, and WTP amongst foreign tourists ranges from RM1.99 to RM11.37. Similar to the destination choice, further analyses on marginal WTP are also discussed. Regarding the local community, this study deduces that community members perceive the tourism industry positively and are willing to participate in tourism-related activities. However, they have some reservations surrounding the presence of tourists in their village, based on social and religious grounds. Their attitudes toward the development of the MP are also positive. Finally this study highlights the economic potentials that players in the tourism industry may tap and capitalize upon, mainly through practising pricing mechanisms in selling and promoting holiday packages in RMP. To the park managers and local authorities, this study may suggest some guidelines for future development processes. Such processes should consider selective development as an option while safeguarding the natural beauty of RMP. The possibility of revising the current conservation fee to resemble tourists’ WTP is also highlighted in this study. Finally, the study recommends the implementation of price discrimination and peak-load pricing in charging and collecting conservation fees as methods, not only for the purposes of increasing revenue but also for acting as tools to monitor and control the number of tourists to RMP.